Determinants of anemia among women of childbearing age: analysis of the 2018 Mali demographic and health survey - Ebenezer Kwesi Armah-Ansah (BMC, 2023)
Abstract Background Anemia occurs at all stages of life and it is of public health concern as it serves as an indicator of quality nutrition and health of a society. Almost one third of the global prevalence of anemia occur among reproductive aged women and almost 40% of these women reside in sub-Saharan Africa including Mali. This study, therefore, sought to assess the determinants of anemia among women of childbearing age in Mali. Methods Secondary data analysis of the 2018 Mali Demographic and health Survey (MDHS). Anemia in women was the outcome variable for the study. Data of 5,048 women aged 15-49 was used for the study. Using binary and multivariate logistic regression models, factors associated with anemia among women were identified. The analysis was conducted using Stata version 14.2 software and adjusted Odds Ratio (aOR) with a 95% Confidence Interval (CI) and p-value < 0.05 were used to see the significant association. Results The prevalence of anemia among women of childbearing age in Mali is 63.5%. Of these, 4.3% and 24.9% were severely and mildly anemic respectively, and the rest 34.3% were moderately anemic. Women who had secondary education (aOR = 0.70, 95% CI: 0.58-0.84), overweight (aOR = 0.63, 95% CI: 0.50-0.81), exposure to mass media (aOR = 0.90, 95% CI = 0.76-1.49) and women with two births (aOR = 0.86, 95% CI = 0.71-1.05) were less likely to be anemic. Likely, richest wealth quintile (aOR = 0.73, 95% CI = 0.51-1.05), living in urban setting (aOR = 0.85, 95% CI = 0.70-1.03) and women in Kidal Region (aOR = 0.42, 95% CI = 0.27-0.65) were less likely to be anemic. However, pregnant women, women covered by health insurance, women with unimproved drinking water, women in communities with low literacy and low socioeconomic status had higher odds of anemia. Conclusion These findings point to the need for community and household level public health sensitization interventions to highlight the pro-anemic factors and mitigating strategies. More especially, women with no education, pregnant women, women covered by health insurance, women from communities with low literacy and socioeconomic status ought to be the focus of such interventions.